History of Activeness in Organizations and Therapeutic Communication Skills in Nursing Profession Students at the Faculty of Nursing, Jember University - Mulyana, Nonica; Purwandari, Retno; Kurniawati, Yulia; Nur, Kholid Rosyidi Muhammad; Afandi, Alfid Tri (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2025)
Background: Organizational involvement plays an important role in enhancing nursing students’ therapeutic communication, a critical competency for future healthcare professionals. Objective: To determine the relationship between organizational activeness and therapeutic communication skills among nursing profession students. Methods: This correlational descriptive-analytical study used a quantitative cross-sectional design involving 171 nursing profession students selected through total sampling. Results: Most students demonstrated a moderate level of organizational activeness (56.1%) and moderate therapeutic communication skills (55.6%). Statistical analysis revealed a significant positive correlation between organizational activeness and therapeutic communication skills (r = 0.521; p < 0.05), indicating that greater participation in organizational activities was associated with better communication performance. Students who were more active in organizations tended to exhibit higher confidence, empathy, and interpersonal awareness during clinical interactions. These findings suggest that active engagement in organizational activities provides opportunities for teamwork, leadership, and communication practice, which are transferable to professional therapeutic communication settings. Conclusion: There is a significant relationship between organizational activeness and therapeutic communication skills, emphasizing that participation in student organizations can enhance professional communication competencies essential for nursing practice.